Tensile properties of polypropylene/linear low-density polyethylene/nano-titanium dioxide nanocomposites using a two-level factorial experiment - Daneshpayeh, Sajjad (Array, 2019)
In this paper, a 23 factorial design analysis was used to study the parameters affecting the mechanical characteristics of polypropylene/linear low-density polyethylene/nano-titanium dioxide (PP/LLDPE/TiO2) nanocomposites, and to optimize these factors in order to predict the maximum ultimate tensile strength (UTS), elastic modulus (EM), and yield strength (YS) simultaneously. To do this, two levels of nano-titanium dioxide (TiO2), linear low-density polyethylene (LLDPE) and styrene-ethylene-butylene-styrene (SEBS) as the coupling agent were selected and eight experiments were conducted for every response. The most effective factors influencing the UTS, EM, and YS were found, and acceptable prediction regression models were taken. One noted that nanoparticles increased the elastic modulus. The attendance of high levels of LLDPE and SEBS resulted in a decrease in YS and UTS. Moreover, the optimum values of variables were determined by using the contour plot.